Anti-Biofouling Effect of PEG-Grafted Block Copolymer Synthesized by RAFT Polymerization - Kim, Seon-Mi; Han, Sang Suk; Kim, A. Young; Choi, Beom-Jin; Paik, Hyun-Jong; Lee, Inwon; Park, Hyun; Chun, Ho Hwan; Cho, Youngjin; Hwang, Do-Hoon (AMER SCIENTIFIC PUBLISHERS, 2015)
Poly(glycidyl methacrylate-block-styrene) (PGMA-b-PS), a block copolymer consisting of glycidyl nnethacrylate and styrene, was synthesized via reversible addition-fragmentation chain transfer living polymerization. The synthesized PGMA-b-PS was then grafted with low-molecular-weight polyethylene glycol (PEG) via epoxy ring opening to give PGMA-g-PEG-b-PS, which was evaluated as an anti-biofouling coating material. As a preliminary test for the anti-biofouling effect, a protein adsorption experiment was performed on the synthesized block copolymer surface. The block copolymers were spin-coated onto silicon wafers, and protein adsorption experiments were carried out using fluorescein isothiocyanate conjugate-labeled bovine serum albumin. The fluorescence intensity of the protein adsorbed on the block copolymer surface was compared with that of a polystyrene film as a reference. The synthesized PGMA-g-PEG-b-PS film showed much lower fluorescence intensity than that of the PS film.